A Model For the Optimum Generation of Employment, Production and income via Priority Sector Advances (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Let us now perceive the variables related to the  borrowers. Their 'job knowledge' is the most dominant  factor. job knowledge pertains to the proficiency of the  borrowers in the methods, processes and procedures of  the activities for which funds have been borrowed. It  further implies the appreciation of jobs of others, and  keeping oneself abreast with the latest developments  having relevance to their activities. These aspects of job  knowledge are as vital as the technical knowledge of the  job. The spectrum of skills required among borrowers is  rather quiet wide. Further it would vary for different  categories of borrowers depending upon the priority  sector to which they belong. The required skills in the  case of farmer-borrower would obviously differ from  those needed in a promoter of small scale industrial unit  or for the same reason, from those which would be  considered essential in a retail/professional/  doctor/lawyer/chartered accountant/ mechanic planning  to start a repair workshop. Even so, certain common  skills of cardinal significance could be mentioned here. It  would be better if borrowers of all categories are well  versed with the mechanism of planning which provides  the desired future state (setting performance standards)  and the means of bringing about the future state. Ability  to take decisions based on unemotional reasoning and  logic, organize and coordinate the resources (gathering  and establishing a proper relationship among the  needed resources), communicate lucidly, monitor  results to manage changes/exigencies for the benefits  are some other skills needed in borrowers irrespective of  the class to which they hail.
Keywords: Optimum Generation; Employment; Production and income